Pengaruh Content Marketing Pada Media Tiktok Shop Terhadap Keputusan Membeli Pada Gen Z - Anindita Putri Salsabila; Alvian Alrasid Ajibulloh (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This study aims to analyze the effect of content marketing on TikTok Shop media on Gen Z's buying decisions. Content marketing is one of the effective marketing strategies in the digital era, especially on social media platforms such as TikTok. In this study, the content marketing indicators used include Relevance, Accuracy, Value, Easy to Understand, Easy to Find, consistency. Meanwhile, purchasing decisions are measured based on indicators of product selection, brand selection, choice of distributor, purchase time, purchase amount, and payment method. The research method used is quantitative with a survey approach. Data was obtained through a questionnaire distributed to 100 Gen Z respondents who actively use TikTok Shop. The data analysis technique used is simple linear regression to see the relationship between content marketing variables and purchasing decisions. The results showed that content marketing on TikTok Shop has a significant effect on Gen Z's buying decision. Factors such as content relevance, trust in influencers, and message consistency are important elements that drive buying decisions.